Automatic Generation of Chinese Short Product Titles for Mobile Display - Gong, Yu; Luo, Xusheng; Zhu, Kenny Q.; Ou, Wenwu; Li, Zhao; Duan, Lu (Proceedings of the AAAI Conference on Artificial Intelligence, 2019)
This paper studies the problem of automatically extracting a short title from a manually written longer description of Ecommerce products for display on mobile devices. It is a new extractive summarization problem on short text inputs, for which we propose a feature-enriched network model, combining three different categories of features in parallel. Experimental results show that our framework significantly outperforms several baselines by a substantial gain of 4.5%. Moreover, we produce an extractive summarization dataset for Ecommerce short texts and will release it to the research community.